Sistem Informasi Stok Opname Berbasis Web Pada PT. Sanoh Indonesia - Suherman; Muhammad Nizar (Prosiding Sains dan Teknologi, 2025)
Data processing in the warehouse at PT. Sanoh Indonesia is essential to support the flow of incoming and outgoing goods. However, operations are still handled manually. Operators record transactions using paper forms and stock cards, while administrators input data into Microsoft Excel without an integrated database. This approach causes inefficiencies, particularly when searching for required data, as it takes considerable time due to the high volume of transactions. This study aims to design a web-based warehouse information system to address issues in recording and retrieving data, especially during stock-taking activities. The system is developed using the Waterfall method and utilizes a centralized database to ensure structured and secure data storage. With the proposed system, stock information can be accessed and printed easily, improving control during stock opname. The processes of receiving and requesting goods can be performed directly and more efficiently, eliminating delays between service and data entry. In addition, inventory availability can be monitored accurately, and reports can be generated and printed based on specific time periods. Overall, the system enhances efficiency, accuracy, and control in warehouse management.